HSP Superfamily of Genes with Emphasis on Their Association with Pyrethroid Resistance in the Malaria Vector Anopheles sinensis (Diptera: Culicidae) - Bin Chen; Feng-Ling Si (Current Overview on Disease and Health Research Vol. 6, 2022)
Heat shock proteins (HSPs) are molecular chaperones that are involved in a variety of normal cellular processes as well as environmental stress. The study looked into the superfamily of genes’ diversity, classification, scaffold location, properties, and phylogenetics, as well as identifying the HSP genes involved with pyrethroid resistance in the Anopheles sinensis genome. Bioinformatic approaches were used to identify the HSP genes in the Anopheles sinensis genome, examine their properties, and establish the phylogenetic relationships of all HSP genes in Anopheles sinensis, Anopheles gambiae, Cx. quinquefasciatus, and Aedes aegypti genomes. Importantly, the work used RNA-seq and RT-qPCR to screen the HSPs related with pyrethroid resistance in three field pyrethroid-resistant populations, and it examined the HSP gene expression pattern in An. sinensis on a time scale after pesticide treatment for the first time. In the genome of An. sinensis, there are 72 HSP genes that are grouped into five families and 11 subfamilies according to molecular weight, homology, and phylogenetics. RNA-seq combining qPCR analysis revealed that the expression level of AsHSP90AB, AsHSP70-2 and AsHSP21.7 are significantly upregulated in at least one field pyrethroid-resistant population. The AsHSP90AB gene is proposed to be essential for pyrethroid stress response in An. sinensis. This paper establishes the framework for the HSP superfamily of genes, laying the groundwork for a better understanding and further investigation of HSP function in insect adaptation to varied environments.